Improving student learning in health science classes: a case study in Thailand - Jinvong, Achara (Curtin University, 2007)
The main purpose of this classroom action research was to improve student learning in a Health Science class in Thailand by using the Constructivist Learning Environment Survey (CLES) and a constructivist learning approach. This study combined quantitative and qualitative data and was conducted over one semester in four stages: 1) assessing the students' perceptions of their constructivist learning environment and determining students' pre-instruction conceptions about AIDS; 2) constructing an intervention based on constructivism theory in order to improving learning environments and students' learning outcomes; 3) implementing the intervention; and 4) evaluating the success of the intervention by re-assessing with the CLES. The Attitude Towards AIDS Questionnaire (ATAQ) was used to assess students' attitudes about AIDS. The students' cognitive achievement was assessed with the Students' Knowledge of AIDS Test (SKAT). Qualitative data were obtained from informal observation, focus group discussions, and student journals. The results indicated that the adapted Thai version of the CLES is appropriate for use in Health Science classes in Thailand's socio-cultural context because it was shown to be valid and reliable in both Actual and Preferred Forms. The results also revealed that the CLES and a constructivist learning approach can be used as effective tools in order to improve the learning environment of a Health Science class. This approach can improve students' knowledge and students' attitudes toward AIDS. The qualitative results supported the results from the questionnaires. This study suggests that teachers and health educators in Thailand can use the CLES to improve their learning environment and use a constructivist learning model to bring about improvement in students' achievement in their classes.